PENGARUH PENGEMBANGAN KARIER DAN PEMBERIAN INSENTIF DALAM MENINGKATKAN KINERJA PEGAWAI - Retnaningrum, Tri Wulandari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to examine the influence of career development and incentive granting in order to improve employeesâ performance. This research is conducted in non-goverment organization (LSM) ISCO Foundation in the city of Surabaya by using quantitative research. The data collection is done by issuing questionnaires. The data is obtained by issuing questionnaires to 60 employees who have the authority in career development and incentive granting at ISCO Foundation and the returned questionnaires are 50 questionnaires. The data quality test is used both validity and reliability test then classic assumption tests which are used in this research are normality test, heterocedacity test, multicolinearity test, and autocorrelation test. Hypothesis test which is used in this research is Adjusted R2 , Simultaneous test (F test), and Partial test (T test). Based on the hypothesis test, the result of research shows that there is positive influence. The independent variable (career development and incentive granting) has an influence to the dependent variable (employeesâ performance) is proved by value of 0,000 and 0,006 which is smaller than significant level at 5%. It proves that employeesâ performance level at ISCO Foundation have high productivity to the career development and incentive granting.Keywords: Career Development, Incentive Granting, Employeesâ Performances